High-performance ultraviolet shielding photoresist based on imine and preparation method thereof
By introducing imine comonomers into the photosensitive resin, a high-performance ultraviolet shielding photoresist with an imine skeleton is solved, and the excellent ultraviolet shielding and mechanics of the photoresist is achieved performance.
Patent Information
- Application Number
- CN202411830691.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-14
AI Technical Summary
Photosensitive resin materials lack ultraviolet shielding properties. Long-term exposure to ultraviolet radiation will lead to photooxidation or photodegradation of photosensitive resin-based polymers, resulting in mechanical properties attenuation, color deterioration and shortening of service life.
By introducing functional monomers containing imine bonds, imine comonomers are prepared and blended with commercial resins to form high-performance ultraviolet shielded photoresist with imine backbone. This method improves the dispersion of comonomers through urethane groups, uses imine to promote the formation of π-π stacking, reduces the energy of the system transition from HOMO to LUMO, and enhances ultraviolet absorption.
It realizes the excellent UV shielding and mechanical properties of photoresist, and can regulate the mechanical properties and UV shielding wavelength range of the final product by regulating the proportion of functional monomers, which is suitable for a variety of application scenarios.
Smart Images

Figure CN119439624A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer chemistry and polymer technology, and more specifically, relates to an imine-based high-performance ultraviolet shielding photoresist and a preparation method thereof. Background Art
[0002] Photosensitive resins are widely used due to their low cost, light weight and ease of processing. Additive manufacturing technology provides a high degree of design flexibility, which further enhances the advantages of photosensitive resins. In particular, two-photon polymerization 3D printing (TPP) has the characteristics of excellent resolution and spatial selectivity, and shows great application potential in micro-nano optics, MEMS, microrobotics and biomedicine. However, compared with inorganic or metal materials, photosensitive resin materials lack UV shielding properties. Long-term exposure to UV radiation can cause photooxidation or photodegradation of photosensitive resin-based polymers, resulting in the attenuation of mechanical properties, deterioration of color and shortened service life. In addition, long-term and large amounts of UV radiation have been proven to be highly correlated with malignant tumors such as melanoma, and the threat of UV to human health is also a topic of widespread concern. Therefore, it is very necessary to develop photosensitive resins with UV shielding capabilities. Generally, various UV absorbers are added to resins to improve their UV shielding properties. These absorbers are generally divided into two categories: blends and comonomers. Blended UV absorbers such as metal oxides and organic dyes provide excellent UV shielding properties. However, during use, the migration of blended type UV absorbers can lead to performance loss and environmental pollution. Comonomer UV absorbers are considered to be a direct and effective strategy to solve these problems. It is worth noting that although the rigid skeleton with large conjugation is beneficial to improve the strength and UV shielding properties of the polymer, it may require a higher diluent ratio or solvent to ensure its compatibility with the resin, limiting its application in two-photon polymerization.
[0003] The present invention proposes a method for preparing a photoresist with excellent ultraviolet shielding and mechanical properties. Urethane groups are used to improve the dispersibility of comonomers in commercial resins, and imines are used to promote the formation of π-π stacking, reduce the energy of the system transition from HOMO to LUMO, and enhance ultraviolet absorption. In addition, π-π stacking and hydrogen bonding are both helpful to increase intermolecular forces and improve mechanical properties. The prepared photosensitive resin has potential application prospects in ultraviolet shielding polymer materials and micro-nano additive manufacturing applications.
[0004] A main technical problem solved by the present invention is to introduce a functional monomer containing an imine bond into a photoresist, thereby giving the photoresist an ultraviolet shielding ability and improving the mechanical properties of the resin. The prepared imine-based copolymer monomer has good compatibility with various commercial resins and a variety of photoinitiators, can be applied to a variety of commercially available photosensitive monomers, and can adjust the mechanical properties and ultraviolet shielding wavelength range of the final cured product by adjusting the proportion of the functional monomers.
[0005] The main process of the preparation method of the high-performance ultraviolet shielding photoresist with an imine skeleton configured by blending functional comonomers based on imine with a variety of basic commercial resins is as follows: firstly, 4-aminophenol and p-hydroxybenzaldehyde or 3-methyl-4-hydroxybenzaldehyde or 3-methoxy-4-hydroxybenzaldehyde or 3-fluoro-4-hydroxybenzaldehyde or 3-chloro-4-hydroxybenzaldehyde or 3-bromo-4-hydroxybenzaldehyde or 3-iodo-4-hydroxybenzaldehyde are reacted to obtain an iminobisphenol intermediate, and then the intermediate is reacted with isocyanoethyl methacrylate or isocyanoethyl acrylate to obtain a comonomer with an imine and a photosensitive group, and then the comonomer is mixed with a multifunctional acrylate monomer under heating conditions, and stirred and mixed, and finally, a light-initiator is added, and the mixture is heated, stirred and mixed to obtain a stable and uniform photoresist. The photoresist can be processed and formed by conventional ultraviolet curing, and can also be processed and formed by additive manufacturing technology to obtain a micro-nanostructure material with ultraviolet shielding ability and excellent mechanical properties. Summary of the invention
[0006] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0007] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a high-performance ultraviolet shielding photoresist based on imide is provided, comprising the following steps:
[0008] Step 1, preparing an intermediate imino diphenol, and using the intermediate imino diphenol to synthesize an imino comonomer;
[0009] Step 2, blending the imine comonomer with the resin to obtain a photoresist precursor;
[0010] Step 3: Blend the photoresist precursor and the initiator to obtain a high-performance UV-shielding photoresist.
[0011] Preferably, in the step 1, the specific method for synthesizing the imine-based comonomer comprises:
[0012] S11. Under anhydrous and oxygen-free conditions and argon protection, 4-aminophenol, a chemical structure of The aldehyde and solvent are added to the reaction container, the temperature is raised to react, and the reaction is continued with stirring, condensation and reflux. After the reaction is completed, the reaction is naturally cooled, and the solution is dropped into petroleum ether or n-hexane for precipitation, and then stirred and filtered. The filter residue is collected, rinsed and vacuum dried to obtain the intermediate imino diphenol;
[0013] S12. Under anhydrous and oxygen-free conditions and argon protection, the intermediate iminodiphenol and isocyanoethyl methacrylate or isocyanoethyl acrylate are reacted in a reaction solvent in the presence of a catalyst; the reaction is condensed and refluxed at 50° C. for 12 to 16 hours, and the reaction is precipitated in petroleum ether or n-hexane after natural cooling. The reaction is filtered and washed after stirring, and the filter residue is collected and vacuum dried to obtain an imino copolymer monomer.
[0014] Preferably, in said S11, the chemical structural formula is In the aldehyde, R is one of -H, -CH3, -OCH3, -F, -Cl, -Br, -I, that is, the aldehyde is one of p-hydroxybenzaldehyde, 3-methyl-4-hydroxybenzaldehyde, 3-methoxy-4-hydroxybenzaldehyde, 3-fluoro-4-hydroxybenzaldehyde, 3-chloro-4-hydroxybenzaldehyde, 3-bromo-4-hydroxybenzaldehyde or 3-iodo-4-hydroxybenzaldehyde;
[0015] The solvent used for synthesizing the intermediate iminodiphenol is methanol or ethanol.
[0016] Preferably, in said S11, the usage ratio of 4-aminophenol, aldehydes and solvent is 1 mmol:1 mmol:2 mL.
[0017] Preferably, in S12, the catalyst is dibutyltin dilaurate, and the reaction solvent is tetrahydrofuran;
[0018] In the above S12, the usage ratio of the intermediate iminodiphenol, isocyanoethyl methacrylate or isocyanoethyl acrylate, the catalyst and the reaction solvent is 1 mmol:3 mmol:1 mg:3-4 mL.
[0019] Preferably, the resin in step 2 is a multifunctional acrylate; step 2 specifically comprises the following method: mixing an imine copolymer monomer and a multifunctional acrylate monomer in a mass ratio of 0-30:70-100, heating to 50° C. and stirring to obtain a photoresist precursor;
[0020] The multifunctional acrylate is a mixture of one or more of bisphenol A epoxy acrylate, tripropylene glycol diacrylate, bisphenol A propylene glycol dimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate and hexanediol diacrylate.
[0021] Preferably, in step 3, the initiator is a photoinitiator, and the amount of the photoinitiator is 0.5% to 2.0% of the mass of the photoresist precursor;
[0022] The photoinitiator is ethyl 2,4,6-trimethylbenzoylphenylphosphonate (hereinafter referred to as TPO-L), bis(4-((4-(diphenylamino)phenyl)ethynyl)phenyl)methanone (hereinafter referred to as BT-TPAA), 4,4'-bis(dimethylamino)benzophenone (hereinafter referred to as DEAK), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (hereinafter referred to as 819), bis(4-((10-hexyl-10H-phenothiazine-3-yl)ethynyl)phenyl)methanone (hereinafter referred to as BT-PTAA-C6), bis(4-((4-(diphenylamino)phenyl)ethynyl)phenyl)methanone (hereinafter referred to as BT-TP ...methylamino)benzophenone) A mixture of one or more of (4-((9-hexyl-9H-carbazole-3-yl)ethynyl)phenyl)methanone (hereinafter referred to as BT-CAA-C6), bis(4-((9-benzyl-9H-carbazole-3-yl)ethynyl)phenyl)methanone (hereinafter referred to as BT-CAA-BN), 4,4'-(10-hexyl-10-H-phenothiazine-3,7-diyl)bis(ethynyl-2,1-diyl)bis(N,N-diphenylaniline) (hereinafter referred to as PTAA-TPAA) or 1-hydroxycyclohexylphenyl ketone (hereinafter referred to as 184).
[0023] A high-performance ultraviolet shielding photoresist based on imine is prepared by a preparation method of the high-performance ultraviolet shielding photoresist based on imine.
[0024] A UV shielding polymer material, the preparation method of which comprises: placing a high-performance UV shielding photoresist into a polytetrafluoroethylene mold or a silicone mold, and preparing the UV shielding polymer material with excellent mechanical properties, molding effect and UV shielding ability through UV curing; wherein the light source used for UV curing is a 405nm LED surface light source, and the irradiation time of the 405nm LED surface light source is 20 to 60 minutes.
[0025] A micro-nano structure material, the preparation method of which comprises: designing a three-dimensional structure through 3D modeling, and preparing a high-performance ultraviolet shielding photoresist through two-photon polymerization additive manufacturing technology to obtain a high-performance ultraviolet shielding micro-nano structure with excellent mechanical properties and molding effect; the micro-nano structure material is applied to multi-scale, multi-material, and multi-dimensional micro-nano functional devices and their structural supports.
[0026] The present invention has at least the following beneficial effects:
[0027] The imine-based comonomer containing imine and urethane groups prepared by the present invention has urethane groups providing hydrogen bonding sites to increase compatibility, imines induce the formation of π-π stacking, and the formation of weak intermolecular interactions (hydrogen bonding and π-π stacking) reduces the energy required for the system to transition from HOMO to LUMO, which improves the ultraviolet shielding ability of the polymer; in addition, the rigid skeleton of the imine conjugated with the benzene ring enhances the strength of the polymer; the weak intermolecular interactions increase the energy dissipation capacity of the polymer, and the prepared photoresist has excellent ultraviolet shielding performance and mechanical properties after curing. The ultraviolet shielding wavelength range, mechanical properties, printing effect and other parameters of the final resin can be regulated by regulating the mass proportion of the comonomers, and can be flexibly changed according to its final application scenario, with a very broad application prospect.
[0028] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The synthetic route diagram of IUMA and MIUMA in Example 1 and Example 2;
[0030] Figure 2 The H NMR spectrum of IUMA prepared in Example 1;
[0031] Figure 3 P(EA) after curing in Example 1 d ) Photograph of polymer dumbbell-shaped specimen;
[0032] Figure 4 P(EA) after curing in Example 1 d -IUMA2) Photograph of polymer dumbbell-shaped specimen;
[0033] Figure 5 P(EA) after curing in Example 1 d -IUMA4) Photograph of polymer dumbbell-shaped specimen;
[0034] Figure 6 P(EA) after curing in Example 1 d -IUMA6) Photograph of polymer dumbbell-shaped specimen;
[0035] Figure 7 P(EA) after curing in Example 1 d -IUMA8) Photograph of polymer dumbbell-shaped specimen;
[0036] Figure 8 P(EA) after curing in Example 1 d -IUMA 10 ) Photograph of polymer dumbbell-shaped specimen;
[0037] Fig. 9 is P(EA in Example 1 d )~P(EA d -IUMA 10 ) Stress-strain curves of polymer dumbbell splines;
[0038] Fig.10 is P(EA in Example 1 d )~P(EA d -IUMA 10 ) Mechanical properties test results of polymer dumbbell-shaped specimens;
[0039] Fig.11 is the EA in Example 1 d and P(EA d )’s FI-TR spectra;
[0040] Fig.12 FI-TR spectra of EA8 and P(EA8) in Example 1;
[0041] Fig.13 Schematic diagram of the energy required for the theoretical HOMO to LUMO orbital transition of 4-(((4-((methylcarbamoyl)oxy)phenyl)imino)methyl)phenylmethylcarbamate in Example 1;
[0042] Fig.14 Schematic diagram of the energy required for the theoretical HOMO to LUMO orbital transition of two 4-(((4-((methylcarbamoyl)oxy)phenyl)imino)methyl)phenylmethylcarbamates in Example 1;
[0043] Fig.15 This is a schematic diagram of the theoretical binding energy of two 4-(((4-((methylcarbamoyl)oxy)phenyl)imino)methyl)phenylmethylcarbamates in Example 1;
[0044] Fig.16 The theoretical UV absorption spectra of single and double 4-(((4-((methylcarbamoyl)oxy)phenyl)imino)methyl)phenylmethylcarbamate of Example 1;
[0045] Fig.17 The H NMR spectrum of MIUMA prepared in Example 2;
[0046] Fig.18 P(EA) after curing in Example 2 d -MIUMA2) Photograph of polymer dumbbell-shaped specimen;
[0047] Fig.19 P(EA) after curing in Example 2 d-MIUMA4) Photograph of polymer dumbbell-shaped specimen;
[0048] Fig. 20 P(EA) after curing in Example 2 d -MIUMA6) polymer dumbbell-shaped specimen photos;
[0049] Fig.21 P(EA) after curing in Example 2 d -MIUMA8) polymer dumbbell-shaped specimen photos;
[0050] Fig. 22 P(EA) after curing in Example 2 d -MIUMA 10 ) Photograph of polymer dumbbell-shaped specimen;
[0051] Fig.23 is P(EA in Example 2 d )~P(EA d -MIUMA 10 ) Stress-strain curves of polymer dumbbell splines;
[0052] Fig.24 is P(EA in Example 2 d )~P(EA d -MIUMA 10 ) Mechanical properties test results of polymer dumbbell-shaped specimens;
[0053] Fig.25 EA prepared in Example 3 d In-situ rheological test result curve;
[0054] Fig.26 EA prepared in Example 3 d -IUMA2 in-situ rheological test result curve;
[0055] Fig. 27 EA prepared in Example 3 d -IUMA4 in-situ rheological test result curve;
[0056] Fig.28 EA prepared in Example 3 d -IUMA6 in-situ rheological test result curve;
[0057] Fig.29 EA prepared in Example 3 d -IUMA8 in-situ rheological test result curve;
[0058] Fig.30 EA prepared in Example 3 d -IUMA 10In-situ rheological test result curve;
[0059] Fig.31 EA prepared in Example 3 d -IUMA x Viscosity and IUMA content relationship diagram;
[0060] Fig.32 EA prepared in Example 3 d -IUMA x Relationship between curing time and IUMA content;
[0061] Fig.33 P(EA) with different IUMA concentrations prepared in Example 3 d -IUMA x ) Sample photos;
[0062] Fig.34 P(EA prepared in Example 3 d -IUMA x )’s UV-visible transmittance graph;
[0063] Fig.35 P(EA) at different thicknesses in Example 3 d -IUMA8) UV-visible transmittance diagram;
[0064] Fig.36 is P(EA in Example 3 d -IUMA8) UV shielding test;
[0065] Fig.37 P(EA prepared in Example 4 d ) Nanoindentation test image at a constant displacement of 500 nm;
[0066] Fig.38 P(EA prepared in Example 4 d -IUMA2) Nanoindentation test image at a constant displacement of 500nm;
[0067] Fig.39 P(EA prepared in Example 4 d -IUMA4) Nanoindentation test image at a constant displacement of 500nm;
[0068] Fig.40 P(EA prepared in Example 4 d -IUMA6) Nanoindentation test image at a constant displacement of 500nm;
[0069] Fig.41 P(EA prepared in Example 4 d-IUMA8) Nanoindentation test image at a constant displacement of 500nm;
[0070] Fig.42 P(EA prepared in Example 4 d -IUMA 10 ) Nanoindentation test image at a constant displacement of 500 nm;
[0071] Fig.43 P(EA prepared in Example 4 d ) Nanoindentation test image under a constant load of 2mN;
[0072] Fig.44 P(EA prepared in Example 4 d -IUMA2) Nanoindentation test image under a constant load of 2mN;
[0073] Fig.45 P(EA prepared in Example 4 d -IUMA4) Nanoindentation test image under a constant load of 2mN;
[0074] Fig.46 P(EA prepared in Example 4 d -IUMA6) Nanoindentation test image under a constant load of 2mN;
[0075] Fig.47 P(EA prepared in Example 4 d -IUMA8) Nanoindentation test image under a constant load of 2mN;
[0076] Fig.48 P(EA prepared in Example 4 d -IUMA 10 ) Nanoindentation test image under a constant load of 2mN;
[0077] Fig.49 P(EA prepared in Example 4 d -IUMA x ) hardness and IUMA concentration;
[0078] Fig.50 P(EA prepared in Example 4 d -IUMA x )'s modulus versus IUMA concentration;
[0079] Fig.51 EA prepared in Example 4 d -IUMA6 TPP test light microscope photos and evaluation form;
[0080] Fig.52 EA prepared in Example 4d -IUMA8 TPP test light microscope photos and evaluation form;
[0081] Fig.53 EA prepared in Example 4 d -SEM image of the TPP test result sample of IUMA6;
[0082] Fig.54 The effect of laser power on the EA prepared in Example 4 d -IUMA6 TPP test line width relationship diagram;
[0083] Fig.55 The scanning speed of the EA prepared in Example 4 d -IUMA6 TPP test line width relationship diagram;
[0084] Fig.56 EA prepared in Example 5 under different laser powers d -IUMA6TPP prints light microscopic photos of large samples;
[0085] Fig.57 EA prepared in Example 5 d -Light microscopic photograph of a large sample printed by IUMA8 TPP. DETAILED DESCRIPTION
[0086] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0087] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0088] Example 1
[0089] This embodiment provides a method for preparing a high-performance ultraviolet shielding photoresist based on imide, comprising the following steps:
[0090] Step 1, anhydrous and oxygen-free, under argon protection, add 12.2g p-hydroxybenzaldehyde (100mmol), 10.9g p-aminophenol (100mmol) and 200mL anhydrous ethanol into a 500mL three-necked bottle, heat to 50°C, condense and reflux for 4h. After the reaction is completed, drop the solution into 200mL of rapidly stirred petroleum ether or medium to precipitate, filter and take the filter residue, rinse the filter residue with dichloromethane and dry it in vacuum at 30°C to obtain the intermediate imino diphenol (IBP). 2.13g intermediate imino diphenol (10mmol), 4.23mL isocyanoethyl methacrylate (30mmol), 10mg catalyst dibutyltin dilaurate are added to the reaction system, 40mL anhydrous tetrahydrofuran is used as solvent, and condense and reflux at 50°C for 16h. After natural cooling, the mixture was dropped into 100 mL of petroleum ether to precipitate, and the residue was collected by filtration. The powder was washed with dichloromethane, and the powder was dried in a vacuum oven away from light to obtain the product 2-((4-((4-(((2-(methacryloyloxy)ethyl)carbamoyl)oxy)benzylidene)amino)phenoxy)carbonyl)amino)ethyl methacrylate (IUMA). The synthesis equation of the product is as follows: Figure 1 As shown, the H NMR spectrum is Figure 2 As shown;
[0091] Step 2: Mix commercial bisphenol A epoxy acrylate and tripropylene glycol diacrylate in a mass ratio of 80:20 and set aside. The resulting mixed resin is recorded as EA. d ;
[0092] Step 3: Combine the IUMA obtained in step 1 with the EA obtained in step 2 d According to IUMA:EA d =0:100, 2:98, 4:96, 6:94, 8:92 and 10:90 in a mass ratio to obtain photoresist precursors with different IUMA contents;
[0093] Step 4: Add 1.5 wt% of the photoinitiator TPO-L to the photoresist precursor obtained in step 3, heat to 50°C and mix well under light protection, stir for 1 hour, and after the system is uniform and free of bubbles, obtain photoresist EA and d , E.A. d -IUMA2,EA d -IUMA4,EA d -IUMA6,EA d -IUMA8,EA d -IUMA 10 ;
[0094] Step 5: Transfer the photoresist obtained in step 4 to a polytetrafluoroethylene mold, place it under a 405nm LED surface light source for polymerization, and irradiate with ultraviolet light for 30 minutes to obtain a fully cured polymer dumbbell-shaped specimen (such as Figure 3-Figure 8 The prepared polymer has good curing effect and molding speed. d ,EA d -IUMA2,EA d -IUMA4, EA d -IUMA6, EA d -IUMA8, EA d -IUMA 10 The prepared polymers are denoted as P(EA d ), P(EA d -IUMA2), P(EA d -IUMA4), P(EA d -IUMA6), P(EA d -IUMA8), P(EA d -IUMA 10 );
[0095] Step 6: Perform uniaxial tensile test on the polymer obtained in step 5 to test its macroscopic mechanical properties. After curing each photoresist, 7 specimens were prepared and the tensile speed was 1 mm / min. -1 , group uniaxial tensile test, take 5 valid data, P(EA d ), P(EA d -IUMA2), P(EA d -IUMA4), P(EA d -IUMA6), P(EA d -IUMA8), P(EA d -IUMA 10 )'s mechanical properties such as Fig. 9 and Fig.10 As shown, Fig. 9 The horizontal axis represents strain, and the vertical axis represents stress; Fig.10 The horizontal axis in the figure represents the IUMA content, the vertical axis on the left represents the stress, and the vertical axis on the right represents the strain. d -IUMA x ) showed a trend of first increasing and then decreasing, among which P(EA d -IUMA x ) is P(EA d ), P(EA d -IUMA2), P(EA d -IUMA4), P(EAd -IUMA6), P(EA d -IUMA8), P(EA d -IUMA 10 ), x=0,2,4,6,8,10. d ) compared to P(EA d -IUMA8) increased in strength from 67±0.76MPa to 100±1.36MPa, and in toughness from 2.36±0.076MJ·m -3 Increased to 5.01±0.017·MJ·m -3 , the elongation at break increased from 6.57±0.24% to 9.17±0.25%. d and EA d - Fourier transform infrared spectra of IUMA8 photoresist before and after curing (such as Fig.11 and Fig.12 As shown) shows at 1635cm -1 and 808cm -1 The C=C peak almost disappears. EA is calculated by the following formula d - Double bond conversion of IUMA8 resin when cured under 405 nm light (70%).
[0096] DC=1-[(A C=C / A Ar ) Polymer / (A C=C / A Ar ) Monomer ]
[0097] The mechanism of action of IUMA molecules in EA was analyzed by theoretical calculation simulation. In the process of calculation, redundant groups were removed to exclude the influence of methacrylate groups on the calculation. Theoretical simulation calculations were performed on (E)-4-(((4-((methylcarbamoyl)oxy)phenyl)imino)methyl)phenylmethylcarbamate (IU) molecules to understand the role of imino and urethane groups in enhancing mechanical properties and improving UV shielding ability. The structures of single IU molecules (IUs) and two IU molecules (IUd) were optimized using the B3LYP universal function and the 6-31G(d) basis set under DFT-D3 dispersion correction. The single point energies of single IU molecules (IUs) and two IU molecules (IUd) were calculated using the M062X universal function and the def2TZVPP basis set under DFT-D3 dispersion correction and basis set overlap error (BSSE) correction to obtain the theoretical energy required for their orbital transition from HOMO to LUMO and the binding energy of the two IU molecules. The structure-optimized IUs and IUd were subjected to time-dependent density functional theory (TD-DFT) calculations using the B3LYP basis set to obtain their theoretical UV-visible absorption spectra. Fig.13 and Fig.14 As shown in , the formation of intermolecular π-π stacking and double hydrogen bonds reduces the energy required for the transition of the molecule from the HOMO to the LUMO orbital, which may lead to the red shift of UV absorption. Fig.15 As shown, the calculated binding energy between two IU molecules is -108.951 kJ·mol -1 , and shows a characteristic parallel displacement state, the distance between the two π planes is This is consistent with the characteristics of π-π stacking interaction. Fig.16 As shown in Figure 3, the theoretical UV-visible spectra calculation results of IUs and IUd show that after the designed molecules form intermolecular interactions, their theoretical strongest UV absorption wavelength red-shifts from 314 nm to 339 nm.
[0098] Example 2
[0099] This embodiment provides a method for preparing a high-performance ultraviolet shielding photoresist based on imide, comprising the following steps:
[0100] Step 1, anhydrous and oxygen-free, under argon protection, add 12.2g 3-methoxy-4-hydroxybenzaldehyde (100mmol), 10.9g p-aminophenol (100mmol), and 200mL anhydrous ethanol into a 500mL three-necked bottle, heat to 50°C, condense and reflux for 4h. After the reaction is completed, drop the solution into 200mL of rapidly stirred petroleum ether for precipitation, filter and take the filter residue, rinse the filter residue with dichloromethane and dry it in vacuum at 30°C to obtain the intermediate imino diphenol. 2.43g intermediate imino diphenol 10mmol, 4.23mL methacrylate isocyanoethyl ester (30mmol), 10mg catalyst dibutyltin dilaurate are added to the reaction system, 40mL anhydrous tetrahydrofuran is used as solvent, and condense and reflux at 50°C for 16h. After natural cooling, the mixture was dropped into 100 mL of petroleum ether to precipitate, and the residue was collected by suction filtration. The powder was washed with dichloromethane, and the powder was dried in a vacuum oven away from light to obtain the product 2-(((4-((4-(((2-(methacryloyloxy)ethyl)carbamoyl)oxy)-3-methoxybenzylidene)amino)phenoxy)carbonyl)amino)ethyl methacrylate (hereinafter referred to as MIUMA). The synthesis equation of the product is as follows: Figure 1 The H NMR spectrum is shown in the attached Fig.17 shown.
[0101] Step 2: Mix commercial bisphenol A epoxy acrylate and tripropylene glycol diacrylate in a mass ratio of 80:20 for later use. The obtained mixed resin is EA d .
[0102] Step 3: Combine the MIUMA obtained in step 1 with the EA obtained in step 2 d Follow MIUMA:EA d The MIUMA and MIUMA precursors were mixed in a mass ratio of 0:100, 2:98, 4:96, 6:94, 8:92 and 10:90 to obtain photoresist precursors with different MIUMA contents.
[0103] Step 4: Add 1.5 wt% of the photoinitiator TPO-L to the photoresist precursor obtained in step 3, heat to 50°C and mix well under light protection, stir for 1 hour, and after the system is uniform and free of bubbles, obtain photoresist EA and d , E.A. d -MIUMA2, EA d -MIUMA4, EA d -MIUMA6,EA d -MIUMA8,EA d -MIUMA 10 .
[0104] Step 5: The photoresist obtained in step 4 is transferred to a polytetrafluoroethylene mold and placed under a 405nm LED surface light source for polymerization. After irradiation with ultraviolet light for 30 minutes, a completely cured dumbbell-like strip polymer is obtained. The obtained polymer is as shown in Figure 18-Figure 22 As shown, the prepared polymer has good curing effect and molding speed; photoresist EA d ,EA d -MIUMA2, EA d -MIUMA4, EA d -MIUMA6, EA d -MIUMA8, EA d -MIUMA 10 The prepared polymers are denoted as P(EA d ), P(EA d -MIUMA2)、P(EA d -MIUMA4)、P(EA d -MIUMA6)、P(EA d -MIUMA8)、P(EA d -MIUMA 10 );
[0105] Step 6: Perform uniaxial tensile test on the polymer obtained in step 5 to test its macroscopic mechanical properties. After curing each photoresist, 7 specimens were prepared and the tensile speed was 1 mm / min. -1 , group uniaxial tensile performance test, take 5 valid data, the specific test results are as follows Fig.23 and Fig.24 As shown, Fig.23 The horizontal axis represents strain, and the vertical axis represents stress; Fig.24 The horizontal axis in the figure shows the MIUMA content, the vertical axis on the left shows the stress, and the vertical axis on the right shows the strain. d -MIUMA x )'s strength and toughness show a trend of first increasing and then decreasing. d The mechanical properties are best when the ratio is 2:98, which is similar to P(EA d ) compared to P(EA d -MIUMA2) increased in strength from 67±0.76MPa to 80±4.56MPa, and in toughness from 2.36±0.076MJ·m -3 Increased to 3.89±0.39MJ·m -3 , the elongation at break increased from 6.57±0.24% to 9.4±1.25%.
[0106] Example 3
[0107] This embodiment provides a method for preparing a high-performance ultraviolet shielding photoresist based on imide, comprising the following steps:
[0108] Step 1, anhydrous and oxygen-free, under argon protection, add 12.2g p-hydroxybenzaldehyde (100mmol), 10.9g p-aminophenol (100mmol), and 200mL anhydrous ethanol into a 500mL three-necked bottle, heat to 50°C, condense and reflux for 4h. After the reaction is completed, drop the solution into 200mL of rapidly stirred petroleum ether for precipitation, filter and take the filter residue, rinse the filter residue with dichloromethane and dry it in vacuum at 30°C to obtain the intermediate imino diphenol. 2.13g intermediate imino diphenol (10mmol), 4.23mL methacrylate isocyanoethyl ester (30mmol), 10mg catalyst dibutyltin dilaurate are added to the reaction system, 40mL anhydrous tetrahydrofuran is used as solvent, and condense and reflux at 50°C for 16h. After natural cooling, the mixture was dropped into 100 mL of petroleum ether or n-hexane to precipitate. The residue was filtered off and the powder was washed with dichloromethane. The powder was dried in a vacuum oven away from light to obtain the product 2-((4-((4-(((2-(methacryloyloxy)ethyl)carbamoyl)oxy)benzylidene)amino)phenoxy)carbonyl)amino)ethyl methacrylate, which was recorded as IUMA.
[0109] Step 2: Mix commercial bisphenol A epoxy acrylate and tripropylene glycol diacrylate in a mass ratio of 80:20 and set aside. The resulting mixed resin is recorded as EA. d .
[0110] Step 3: Combine the IUMA obtained in step 1 with the EA obtained in step 2 d According to IUMA:EA d The mixture was mixed in a mass ratio of 0:100, 2:98, 4:96, 6:94, 8:92 and 10:90 to obtain photoresist precursors with different IUMA contents.
[0111] Step 4: Add 1.5 wt% of the photoinitiator TPO-L to the photoresist precursor obtained in step 3, heat to 50°C and mix well under light protection, stir for 1 hour, and after the system is uniform and free of bubbles, obtain photoresist EA and d ,EA d -IUMA2, EA d -IUMA4, EA d -IUMA6, EA d -IUMA8, EA d -IUMA 10 .
[0112] Step 5: Test the in-situ curing rheology of the photoresist obtained in step 4 using a xenon lamp (250-450nm, 2.5mW·cm-2 ) as the light source, the results are shown in Figure 25-Figure 30 .like Fig.31 As shown, EA d -IUMA x The average complex viscosity of the d ) increased to 16Pa.s(EA d -IUMA8). Fig.32 As shown in the figure, with the increase of IUMA content, the time required to reach G' / G" = 1 gradually increases, indicating that under the range of low irradiation intensity light source (xenon lamp 250-450nm, 2.5mW·cm -2 ) when solidified with EA d In comparison, EA d -IUMA x It takes more time to cure. This is because IUMA, as a UV-absorbing imine-based comonomer, competes with TPO-L and absorbs part of the UV light, which prolongs the curing time.
[0113] Step 6: The photoresist obtained in step 4 was cured in a customized polytetrafluoroethylene mold in a 405nm LED surface light source UV curing box to prepare polymer blocks with different IUMA mass percentages of 1mm thick, 25mm wide and 60mm long, such as Fig.33 As shown; and its UV-visible light transmittance was tested, as shown Fig.34 As shown, the results showed that the UV shielding ability of the prepared polymer samples was positively correlated with the IUMA concentration.
[0114] Step 7: Use the EA obtained in step 4 d -IUMA8 photoresist was cured in a custom-made polytetrafluoroethylene mold in a 405nm LED surface light source UV curing box to prepare polymer blocks with thicknesses of 0.2, 0.4, 0.6, 0.8 and 1.0 mm, and their UV-visible light transmittance was tested. The results are as follows Fig.35 As shown, P(EA d -IUMA8) UV shielding ability is positively correlated with thickness. Within a certain range, the UV shielding band can be controlled by controlling the thickness of the polymer. d -IUMA8) UV shielding performance, EA containing 1.5wt% TPO-L d Placed in a 5×5×5mm silicone mold, P(EA d -IUMA8) was placed on top of it, and then an LED surface light source (365±10nm, 5mW·cm -2 ) Continuous irradiation, such as Fig.36As shown, the results show that EA d Resin in 1mm thick P(EA d -IUMA8) is completely uncured, indicating that 1mmEA d -IUMA8 has good long-term UV shielding ability. Fig.34 , Fig.35 and Fig.36 P(EA d ), P(EA d -IUMA2), P(EA d -IUMA4), P(EA d -IUMA6), P(EA d -IUMA8), P(EA d -IUMA 10 ) respectively correspond to photoresist EA d ,EA d -IUMA2, EA d -IUMA4, EA d -IUMA6, EA d -IUMA8, EA d -IUMA 10 Cured polymer samples.
[0115] Example 4
[0116] This embodiment provides a method for preparing a high-performance ultraviolet shielding photoresist based on imide, comprising the following steps:
[0117] Step 1, anhydrous and oxygen-free, under argon protection, add 12.2g p-hydroxybenzaldehyde (100mmol), 10.9g p-aminophenol (100mmol), and 200mL anhydrous ethanol into a 500mL three-necked bottle, heat to 50°C, condense and reflux for 4h. After the reaction is completed, drop the solution into 200mL of rapidly stirred petroleum ether for precipitation, filter and take the filter residue, rinse the filter residue with dichloromethane and dry it in vacuum at 30°C to obtain the intermediate imino diphenol. 2.13g intermediate imino diphenol (10mmol), 4.23mL methacrylate isocyanoethyl ester (30mmol), 10mg catalyst dibutyltin dilaurate are added to the reaction system, 40mL anhydrous tetrahydrofuran is used as solvent, and condense and reflux at 50°C for 16h. After natural cooling, the mixture was added dropwise into 100 mL of petroleum ether to precipitate, and the residue was collected by suction filtration. The powder was washed with dichloromethane or ethyl acetate, and the powder was dried in a vacuum oven away from light to obtain the product 2-((4-((4-(((2-(methacryloyloxy)ethyl)carbamoyl)oxy)benzylidene)amino)phenoxy)carbonyl)amino)ethyl methacrylate (IUMA);
[0118] Step 2: Mix commercial bisphenol A epoxy acrylate and tripropylene glycol diacrylate in a mass ratio of 80:20 and set aside. The resulting mixed resin is recorded as EA. d ;
[0119] Step 3: Combine the IUMA obtained in step 1 with the EA obtained in step 2 d According to IUMA:EA d =0:100, 2:98, 4:96, 6:94, 8:92 and 10:90 in a mass ratio to obtain photoresist precursors with different IUMA contents;
[0120] Step 4: Add 0.15 wt% of the photoinitiator TPO-L to the photoresist precursor obtained in step 3, heat to 50°C and mix well under light protection, stir for 1 hour, and obtain photoresist EA after the system is uniform and free of bubbles. d ,EA d -IUMA2, EA d -IUMA4, EA d -IUMA6, EA d -IUMA8, EA d -IUMA 10 .
[0121] Step 5: pour the photoresist obtained in step 4 into a 5×5×5mm silicone mold, and place the silicone mold injected with photoresist under a 405nm LED surface light source for polymerization. After irradiation with ultraviolet light for 30 minutes, a completely cured cubic sample is obtained. A sample with a smooth surface is selected for each ratio to test the nanoindentation in two modes, constant load and constant indentation depth. The load set in the constant load mode is 2mN, and the indentation depth set in the constant indentation depth mode is 500nm. Each test surface is tested more than 7 times, and 5 valid data are taken. The test results are as follows: Figure 37-Figure 48 EA is calculated based on nanoindentation data. d -IUMA x The relationship between IUMA content and modulus and hardness is shown in Fig.49 and Fig.50 With the addition of imine comonomers, the modulus and hardness of the resin first decrease and then increase. This is because the addition of imine comonomers will affect the overall hydrogen bond distribution of the polymer. When the content of imine comonomers is small, fewer weak interactions are formed and the modulus of the polymer decreases. However, as the concentration of functional monomers increases, a large amount of π-π stacking is generated inside the resin after curing, thereby improving the modulus and hardness of the resin. Figure 37-Figure 50 Medium, photoresist EA d ,EA d -IUMA2, EA d-IUMA4, EA d -IUMA6, EA d -IUMA8, EA d -IUMA 10 The solidified samples are denoted as P(EA d ), P(EA d -IUMA2), P(EA d -IUMA4), P(EA d -IUMA6), P(EA d -IUMA8), P(EA d -IUMA 10 ).
[0122] Step 6: Add 0.75 wt% of photoinitiator BT-TPAA to the IUMA:EA obtained in step 3. d The photoresist precursor with a ratio of 6:94 and 8:92 was heated to 50°C under light protection and mixed, and stirred for 1 hour. After the system was uniform and free of bubbles, two-photon photoresist EA was obtained. d -IUMA6 and EA d -IUMA8. Then a two-photon polymerization 3D printing test was conducted. The three-dimensional structure used in the test was a conventional wooden stick pile structure. Two-photon polymerization 3D printing was performed under different laser powers and different printing speeds.
[0123] Step 7: Develop the printed sample obtained in step 6. Soak it in propylene glycol monomethyl ether acetate for 30 minutes, then transfer it to isopropanol and soak it for 10 minutes. Take out the sample and let the developer dry naturally. Optical microscope photos and result evaluation are as follows Fig.51 and Fig.52 As shown, EA d -IUMA6 and EA d -IUMA8 can be applied to various laser powers (5-50mW) and scanning speeds (100-100000μm·s -1 ), with excellent TPP performance. By analyzing the EA after TPP d -SEM images of IUMA6 resin, and the effect of different laser powers and scanning speeds on the polymer line width (e.g. Fig.53 The results show that the line width becomes wider as the laser power increases (as shown in Fig.54 As the scanning speed increases, it becomes narrower (as shown in Fig.55 EA d -IUMA6 can be applied to various laser powers and scanning speeds, with excellent TPP performance.
[0124] Example 5
[0125] This embodiment provides a method for preparing a high-performance ultraviolet shielding photoresist based on imide, comprising the following steps:
[0126] Step 1, anhydrous and oxygen-free, under argon protection, add 12.2g p-hydroxybenzaldehyde (100mmol), 10.9g p-aminophenol (100mmol), and 200mL anhydrous ethanol into a 500mL three-necked bottle, heat to 50°C, condense and reflux for 4h. After the reaction is completed, drop the solution into 200mL of rapidly stirred petroleum ether for precipitation, filter and take the filter residue, rinse the filter residue with dichloromethane and dry it in vacuum at 30°C to obtain the intermediate imino diphenol. 2.13g intermediate imino diphenol (10mmol), 4.23mL methacrylate isocyanoethyl ester (30mmol), 10mg catalyst dibutyltin dilaurate are added to the reaction system, 40mL anhydrous tetrahydrofuran is used as solvent, and condense and reflux at 50°C for 16h. After natural cooling, the mixture was dropped into 100 mL of petroleum ether to precipitate, and the residue was collected by suction filtration. The powder was washed with dichloromethane or ethyl acetate, and the powder was dried in a vacuum condition away from light to obtain the product 2-((4-((4-(((2-(methacryloyloxy)ethyl)carbamoyl)oxy)benzylidene)amino)phenoxy)carbonyl)amino)ethyl methacrylate (IUMA).
[0127] Step 2: Mix commercial bisphenol A epoxy acrylate and tripropylene glycol diacrylate in a mass ratio of 80:20 and set aside. The resulting mixed resin is recorded as EA. d .
[0128] Step 3: Combine the IUMA obtained in step 1 with the EA obtained in step 2 d According to IUMA:EA d The two materials were blended in a mass ratio of 6:94 and 8:92 to obtain photoresist precursors with two IUMA contents.
[0129] Step 4: Add 0.75 wt% of photoinitiator BT-TPAA to the IUMA:EA obtained in step 3. d The photoresist precursor with a ratio of 6:94 and 8:92 was heated to 50°C under light protection and mixed, and stirred for 1 hour. After the system was uniform and free of bubbles, two-photon photoresist EA was obtained. d -IUMA6,EA d -IUMA8.
[0130] Step 5: Testing the EA d -IUMA6 at a fixed scanning speed of 50000 μm·s -1 , TPP printed 100μm samples at different powers. d -IUMA8 at a fixed scanning speed of 10000 μm·s-1 , TPP printed 200μm samples at different powers.
[0131] Step 6: Develop the printed sample obtained in step 5. Soak it in propylene glycol monomethyl ether acetate for 30 minutes, then transfer it to isopropanol and soak it for 10 minutes. Take out the sample and let the developer dry naturally. d -IUMA6 performs TPP printing of relatively large size at fixed speed and different powers. Optical microscope photos such as Fig.56 As shown, EA d -IUMA8 performs TPP printing of relatively large size at fixed speed and different powers. Optical microscope photos Fig.57 As shown, the results show that EA d -IUMA6,EA d -IUMA8 can print relatively large devices through TPP.
[0132] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention are obvious to those skilled in the art. Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation mode. They can be applied to various fields suitable for the present invention. For those familiar with the art, other modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to the specific details and the legends shown and described here.
Claims
1. A method for preparing a high-performance ultraviolet shielding photoresist based on imide, characterized in that: The following steps are involved: Step 1, preparing an intermediate imino diphenol, and using the intermediate imino diphenol to synthesize an imino comonomer; Step 2, blending the imine comonomer with the resin to obtain a photoresist precursor; Step 3: Blend the photoresist precursor and the initiator to obtain a high-performance UV-shielding photoresist.
2. The method for preparing a high-performance ultraviolet shielding photoresist based on imide according to claim 1, characterized in that: The specific method of step one includes: S11. Under anhydrous and oxygen-free conditions and argon protection, 4-aminophenol, a chemical structure of The aldehyde and solvent are added to the reaction container, the temperature is raised to react, and the reaction is continued with stirring, condensation and reflux. After the reaction is completed, the reaction is naturally cooled, and the solution is dropped into petroleum ether or n-hexane for precipitation, and then stirred and filtered. The filter residue is collected, rinsed and vacuum dried to obtain the intermediate imino diphenol; S12. Under anhydrous and oxygen-free conditions and argon protection, the intermediate iminodiphenol and isocyanoethyl methacrylate or isocyanoethyl acrylate are reacted in a reaction solvent in the presence of a catalyst; the reaction is condensed and refluxed at 50° C. for 12 to 16 hours, and the reaction is precipitated in petroleum ether or n-hexane after natural cooling. The reaction is filtered and washed after stirring, and the filter residue is collected and vacuum dried to obtain an imino copolymer monomer.
3. The method for preparing a high-performance ultraviolet shielding photoresist based on imine according to claim 2, characterized in that: In S11, the chemical structural formula is In the aldehyde, R is one of -H, -CH3, -OCH3, -F, -Cl, -Br, -I, that is, the aldehyde is one of p-hydroxybenzaldehyde, 3-methyl-4-hydroxybenzaldehyde, 3-methoxy-4-hydroxybenzaldehyde, 3-fluoro-4-hydroxybenzaldehyde, 3-chloro-4-hydroxybenzaldehyde, 3-bromo-4-hydroxybenzaldehyde or 3-iodo-4-hydroxybenzaldehyde; The solvent used for synthesizing the intermediate iminodiphenol is methanol or ethanol.
4. The method for preparing a high-performance ultraviolet shielding photoresist based on imide according to claim 2, characterized in that: In the S11, the usage ratio of 4-aminophenol, aldehydes and solvent is 1 mmol:1 mmol:2 mL.
5. The method for preparing a high-performance ultraviolet shielding photoresist based on imide according to claim 2, characterized in that: In S12, the catalyst is dibutyltin dilaurate, and the reaction solvent is tetrahydrofuran; In the above S12, the usage ratio of the intermediate iminodiphenol, isocyanoethyl methacrylate or isocyanoethyl acrylate, the catalyst and the reaction solvent is 1 mmol:3 mmol:1 mg:3-4 mL.
6. The method for preparing a high-performance ultraviolet shielding photoresist based on imide according to claim 1, characterized in that: The resin in step 2 is a multifunctional acrylate; step 2 specifically comprises the following method: mixing an imine copolymer monomer and a multifunctional acrylate monomer in a mass ratio of 0-30:70-100, heating to 50° C. and stirring to obtain a mixed resin; The multifunctional acrylate is a mixture of one or more of bisphenol A epoxy acrylate, tripropylene glycol diacrylate, bisphenol A propylene glycol dimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate and hexanediol diacrylate.
7. The method for preparing a high-performance ultraviolet shielding photoresist based on imide according to claim 1, characterized in that: In the step 3, the initiator is a photoinitiator, and the amount of the photoinitiator is 0.5% to 2.0% of the mass of the mixed resin; The photoinitiator is one or more mixtures of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, bis(4-((4-(diphenylamino)phenyl)ethynyl)phenyl)ketone, 4,4'-bis(dimethylamino)benzophenone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, bis(4-((10-hexyl-10H-phenothiazine-3-yl)ethynyl)phenyl)ketone, bis(4-((9-hexyl-9H-carbazole-3-yl)ethynyl)phenyl)ketone, bis(4-((9-benzyl-9H-carbazole-3-yl)ethynyl)phenyl)ketone, 4,4'-(10-hexyl-10-H-phenothiazine-3,7-diyl)bis(ethynyl-2,1-diyl)bis(N,N-diphenylaniline) or 1-hydroxycyclohexylphenylketone.
8. A high-performance ultraviolet shielding photoresist based on imide, characterized in that: The photoresist is prepared by the method for preparing the high-performance ultraviolet shielding photoresist based on imine according to any one of claims 1 to 7.
9. A UV shielding polymer material prepared from the high-performance UV shielding photoresist based on imide according to claim 8, characterized in that: The preparation method of the ultraviolet shielding polymer material comprises: placing a high-performance ultraviolet shielding photoresist into a polytetrafluoroethylene mold or a silicone mold, and preparing the ultraviolet shielding polymer material by ultraviolet curing; wherein the light source used for ultraviolet curing is a 405nm LED surface light source, and the irradiation time of the 405nm LED surface light source is 20 to 60 minutes.
10. A micro-nanostructure material prepared from the high-performance ultraviolet shielding photoresist based on imide according to claim 8, characterized in that: The preparation method of the micro-nano structure material comprises: designing a three-dimensional structure through 3D modeling, preparing and molding a high-performance ultraviolet shielding photoresist through two-photon polymerization additive manufacturing technology to obtain a micro-nano structure; the micro-nano structure material is applied to multi-scale, multi-material, and multi-dimensional micro-nano functional devices and their structural support parts.